Pengaruh Terpaan Media Instagram Terhadap Perubahan Sikap Untuk Hidup Sehat - Sumampouw, Lingkan Feibe (Dinasti Research & Yayasan Dharma Indonesia Tercinta (DINASTI), 2023)
A healthy lifestyle is still a necessity that is maintained by the community. Many messages are disseminated through online media as one of the information that must be known by the public. One of the media that can be used to disseminate this information is Instagram media using the @hidup_sehat_bahagia account. It is hoped that this post can provide education and have a positive impact on changes in follower attitudes. This study aims to analyze and determine the exposure of Instagram media to changes in attitudes to healthy living through food, drink, and exercise. This study uses Social Appraisal theory, using an understanding of media exposure and attitude change. Quantitative research approach, explanatory research nature, and survey research method. The research was conducted on 100 samples of respondents who were part of followers of the @hidup_sehat_bahagia account. The information from the Correlation Test reveals a robust connection between time spent consuming media and mental shifts. While the results of the hypothesis obtained there is an influence between exposure to Instagram media on changes in the attitude of followers of the @hidup_sehat_bahagia account.